The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1158/0008-5472.can-06-1986
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2 Fusions with Oncogenic ETS Factors in Prostate Cancer Involve Unbalanced Genomic Rearrangements and Are Associated with HDAC1 and Epigenetic Reprogramming

Abstract: Translocations fusing the strong androgen-responsive gene, TMPRSS2, with ERG or other oncogenic ETS factors may facilitate prostate cancer development. Here, we studied 18 advanced prostate cancers for ETS factor alterations, using reverse transcription-PCR and DNA and RNA array technologies, and identified putative ERG downstream gene targets from the microarray data of 410 prostate samples. Out of the 27 ETS factors, ERG was most frequently overexpressed. Seven cases showed TMPRSS2:ERG gene fusions, whereas … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
152
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(168 citation statements)
references
References 20 publications
14
152
0
2
Order By: Relevance
“…When this fusion has occurred, the 3 0 -centromeric and 5 0 -telomeric ends of ERG occur as separated red and green signals (Figure 1b; Tomlins et al, 2005;Perner et al, 2006). Many cancers with alteration in the ERG gene FISH pattern also exhibit loss of the lone green 5 0 -ERG signal (Figures 1c-e), consistent with previous findings that the chromosomal region between TMPRSS2 and ERG on chromosome 21 is frequently deleted in cancers with TMPRSS-ERG fusions (Iljin et al, 2006;Perner et al, 2006).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…When this fusion has occurred, the 3 0 -centromeric and 5 0 -telomeric ends of ERG occur as separated red and green signals (Figure 1b; Tomlins et al, 2005;Perner et al, 2006). Many cancers with alteration in the ERG gene FISH pattern also exhibit loss of the lone green 5 0 -ERG signal (Figures 1c-e), consistent with previous findings that the chromosomal region between TMPRSS2 and ERG on chromosome 21 is frequently deleted in cancers with TMPRSS-ERG fusions (Iljin et al, 2006;Perner et al, 2006).…”
Section: Resultssupporting
confidence: 89%
“…The failure to observe worse clinical outcome in class Esplit cancers indicates that the loss of sequences 5 0 to ERG found in Edel cancers is also critical to cancer aggression. It has been shown by several groups (Hermans et al, 2006;Iljin et al, 2006;Perner et al, 2006) that fusion of the tandemly arranged TMPRSS2 and ERG fusions in prostate cancer is frequently accompanied by loss of the entire intervening chromosome 21 sequence, so a search of this region for genes with a tumour-suppressive effect may be a fruitful avenue of future investigation. Wang et al (2006) have provided evidence that the presence of a particular fusion transcript between exon 2 of TMPRSS2 and exon 4 of ERG that encodes a TMPRSS2-ERG fusion protein may also be associated with aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently unclear whether this microdeletion of chromosome 21q would carry additional biological significance beyond the ERG activation, a view that was recently entertained. 16,17 The finding that TMPRSS2-ETS fusion is seen in approximately half of the prostate cancer also raises the issue of whether the fusion-positive and fusion-negative cases would differ biologically, for instance, in their histomorphology, response to treatment or prognosis. Previous studies have shown no correlation to Gleason's grades, lymph node status or clinical stages, 16 and Demichelis et al 21 suggested that TMPRSS2-ERG fusion-positive carcinomas might represent a more aggressive phenotype.…”
Section: Tmpress2-erg In Prostate Cancer Jj Tu Et Almentioning
confidence: 99%
“…15 Thus, the TMPRSS2-ERG fusion could result either from balanced or unbalanced translocation, or from deletion of the intervening DNA segment, and the literature to date suggests deletion as the more frequent event. 16,17 In the present study, we evaluated a series of 82 formalin-fixed paraffin-embedded prostate cancer specimens, by RT-PCR and by FISH analyses. TMPRSS2-ERG fusion was observed in 43% of the cases, more commonly resulting from deletion than translocation.…”
mentioning
confidence: 99%